Intended and unintended consequences of mandatory IFRS adoption: A review of extant evidence and suggestions for future research - Ulf Brüggemann; Jörg-Markus Hitz; Thorsten Sellhorn (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
This paper discusses empirical evidence on the economic consequences of mandatory adoption of International Financial Reporting Standards (IFRS) in the European Union (EU) and provides suggestions on how future research can add to our understanding of these effects. Based on the explicitly stated objectives of the EU's so-called 'IAS Regulation', we distinguish between intended and unintended consequences of mandatory IFRS adoption. Empirical research on the intended consequences generally fails to document an increase in the comparability or transparency of financial statements. In contrast, there is rich and almost unanimous evidence of positive effects on capital markets and at the macroeconomic level. We argue that certain research design issues are likely to contribute to this apparent mismatch in findings and we suggest areas for future research to address it. The literature investigating unintended consequences of mandatory IFRS adoption is still in its infancy. However, extant empirical evidence and insights from non-IFRS settings suggest that mandatory IFRS adoption has the potential to materially affect contractual outcomes. We conclude that both the intended and the unintended consequences deserve further scrutiny to assess the costs and benefits of mandatory IFRS adoption, which may help provide a basis for evaluating the effectiveness of the IAS Regulation. We provide specific guidance for future research in this field.
Keywords: G38; K12; K22; K34; M41; M48; 330; international accounting; IFRS adoption; economic consequences; contracting; regulation; review; International Financial Reporting Standards; Publizitätspflicht; Bilanzrecht; Rechtsangleichung; Kosten-Nutzen-Analyse; Welt